2005
DOI: 10.1021/ja044885g
|View full text |Cite
|
Sign up to set email alerts
|

Selective Small Molecules Blocking HIV-1 Tat and Coactivator PCAF Association

Abstract: Development of drug resistance from mutations in the targeted viral proteins leads to continuation of viral production by chronically infected cells, contributing to HIV-mediated immune dysfunction. Targeting a host cell protein essential for viral reproduction, rather than a viral protein, may minimize the viral drug resistance problem as observed with HIV protease inhibitors. We report here the development of a novel class of N1-aryl-propane-1,3-diamine compounds using a structure-based approach that selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
143
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 16 publications
2
143
0
2
Order By: Relevance
“…This strategy was first suggested for controlling HIV-1 transcriptional activation and replication in infected host cells (Zeng et al 2005). Transcriptional activation of the integrated HIV provirus requires a molecular interaction between the HIV-1 Tat trans-activator, acetylated at lysine 50 and the bromodomain of the host transcriptional coactivator PCAF (Dorr et al 2002;Mujtaba et al 2002), suggesting that blocking this host-virus interaction could result in a reduction in Tat-mediated viral transcription.…”
Section: Pharmacological Inhibition Of Bromodomains In Gene Transcripmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy was first suggested for controlling HIV-1 transcriptional activation and replication in infected host cells (Zeng et al 2005). Transcriptional activation of the integrated HIV provirus requires a molecular interaction between the HIV-1 Tat trans-activator, acetylated at lysine 50 and the bromodomain of the host transcriptional coactivator PCAF (Dorr et al 2002;Mujtaba et al 2002), suggesting that blocking this host-virus interaction could result in a reduction in Tat-mediated viral transcription.…”
Section: Pharmacological Inhibition Of Bromodomains In Gene Transcripmentioning
confidence: 99%
“…Indeed, small-molecule bromodomain inhibitors such as N1-aryl-propane-1,3-diamine compounds (Fig. 9A) were shown to be able to block PCAF bromodomain binding to K50-acetylated HIV-1 Tat in cells and effectively attenuate Tat-mediated HIV transcriptional activation (Zeng et al 2005;Pan et al 2007). …”
Section: Pharmacological Inhibition Of Bromodomains In Gene Transcripmentioning
confidence: 99%
“…Using the structure-guided methods, small molecule chemical ligands have been developed which are shown to be capable of selectively blocking the PCAF bromodomain binding to HIV-1 Tat at the acetylatedlysine 50 (Zeng et al, 2005) or the CBP bromodomain binding to human tumor suppressor p53 at the acetylated-lysine 382 (Sachchidanand et al, 2006). The structural analysis revealed that both PCAF and CBP specific lead compounds, that is NP1 (N1-4-methyl-2-nitro-phenyl-propane-1,3-diamine) (Figures 2a and b) and MS7972 (9-acetyl-2,3,4,9-tetrahydro-carbazol-1-1) (Figures 2c and d), respectively, are situated at the entrance of the acetyl-lysine binding pocket by interacting with amino-acid residues in the ZA loop of the corresponding protein (Figures 2a and b), thereby blocking the bromodomain interaction with its biological target protein.…”
Section: Small Molecules Modulating Biological Functions Of the Bromomentioning
confidence: 99%
“…Another direction in epigenetic drug discovery might be to target interactions between histone binding modules and their cognate binding partners. There have already been reports of small molecules that block the interaction between bromodomains and nonhistone proteins such as HIV-1 Tat [87,88] and p53 [89]. Further study of the biological modes of action of epigenetic modulators and the continued identification of new epigenetic biomarkers will be essential.…”
Section: Ink4amentioning
confidence: 99%